Appendix to Staging the Spanish Golden Age: Translation and Performance (Verse Charts) - Jeffs, K (University of Oxford, 2015)
The purpose of these charts is to visually communicate shifts of verse form in the plays staged during the Royal Shakespeare Company's 2004-2005 season to academicians and theatre practitioners working with the plays in both the original Spanish and in English translation. This material is intended to supplement the monograph, particularly for the chapter dedicated to versification. There is a set of charts for each play that received a full production in the RSC's Spanish Golden Age Season, with one page for each act. Further information is included in the introductory material in the first few pages of the file. The research is based on work carried out towards the D.Phil. thesis supervised by Jonathan Thacker of Merton College.